Extending the Theory of Planned Behavior: The Dual Role of Social Media Interaction in Sustainable Fashion Purchase Intention - Gusti, Yenny Kurnia; Insiatiningsih, Insiatiningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
Despite the growing influence of social media on sustainable consumption, its theoretical integration within the Theory of Planned Behavior (TPB) remains limited. Prior studies largely treat social media as an external communication channel rather than as a structural component of behavioral intention models. This study extends TPB by conceptualizing social media interaction as both an antecedent of attitude, subjective norm, and perceived behavioral control, and as a moderator of the intention formation process in sustainable fashion consumption. Using survey data from 300 Indonesian social media users and Structural Equation Modeling (SEM), the findings indicate that social media interaction significantly influences all TPB constructs. Perceived behavioral control emerges as the strongest predictor of purchase intention. Moderation analysis reveals that social media interaction strengthens the attitude–intention relationship, does not significantly affect the norm–intention relationship, and weakens the control–intention relationship. The study contributes to theory by offering a digitally contextualized extension of TPB and highlights the importance of structured and interactive social media strategies in promoting sustainable fashion consumption.